Pengaruh Literasi Keuangan dan Self Efficacy Terhadap Perilaku Keuangan yang Dimoderasi Gender pada Owner UMKM di Desa Gintung Kerta - Abdulloh; Ujang Suherman; Rengga Madya Pranata (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The focus objective this study is to find out The manner in which financial literacy and independence influence the financial behavior of small and medium enterprise (MSME) owners. in Gintung Kerta village which is gender moderated. This research is quantitative. This research involved the owners of 138 MSMEs in Gintung Kerta village, with a sample of 103 of them. Data was collected using a purposive sampling method. Questionnaire via gform and multiple regression analysis were used. The results of the study show that financial literacy significantly influences the financial actions of MSME owners in Gintung Kerta village, while self-efficacy also influences the financial behavior of MSME owners in Gintung Kerta village. Financial literacy and self-efficacy have a significant simultaneous influence on the financial behavior of MSME owners in Gintung Kerta village. Gender is unable to influence The impact of financial conduct on financial literacy among MSME owners in Gintung Kerta village. Gender is unable to influence self-efficacy on financial behavior among MSME owners in Gintung Kerta village